2017
DOI: 10.1111/jvim.14820
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Prednisone Administration on Serum Cystatin C in Dogs

Abstract: BackgroundOral administration of glucocorticoid alters serum cystatin C (sCysC) concentration in humans.ObjectiveTo determine if oral administration of prednisone alters sCysC in dogs without pre‐existing renal disease.AnimalsForty six dogs were included: 10 dogs diagnosed with steroid responsive meningitis arteritis (SRMA; group A), 20 dogs diagnosed of pituitary‐dependent hyperadrenocorticism (PDH; group B), and 16 healthy control dogs (group C).MethodsRetrospective observational study. SRMA diagnosed dogs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
1
11
0
1
Order By: Relevance
“…Bjarnadottir et al demonstrated in vitro that dexamethasone could lead to CysC level increase by the dose-dependent manner [ 23 ]. Recent studies confirmed this in animals [ 24 , 25 ], and we found similar results in our current study. We found that sCysC level in glucocorticoid users was higher than that in non-users, no matter with or without matching.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Bjarnadottir et al demonstrated in vitro that dexamethasone could lead to CysC level increase by the dose-dependent manner [ 23 ]. Recent studies confirmed this in animals [ 24 , 25 ], and we found similar results in our current study. We found that sCysC level in glucocorticoid users was higher than that in non-users, no matter with or without matching.…”
Section: Discussionsupporting
confidence: 93%
“…However, it was shown that glucocorticoids could stimulate the production of CysC in vitro [ 23 ]. Moreover, glucocorticoid medication would also increase sCysC concentrations in experimental animals, such as rats and dogs [ 24 , 25 ]. Glucocorticoids have extensive applications in human medicine because of its functions of anti-inflammation and immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…However, serum Cre concentrations are more stable within a single individual than are measurements of SDMA and CysC [19,28]. Serum CysC concentrations can be increased by various extrarenal factors, including administration of prednisolone [27], hyperadrenocorticism [21]. In our study, serum CysC concentrations correlated directly with body weight; dogs that weighed < 20 kg had significantly lower levels of serum Cre and serum CysC than did dogs that weighed ≥ 20kg.…”
Section: Discussionmentioning
confidence: 51%
“…In this study, we excluded dogs that had been treated with prednisolone [27] or diagnosed with hyperadrenocorticism [21] or thyroid disease [11,34]; likewise, we excluded dogs that were obese, overly thin, or had a history of weight loss prior to the study initiation [31]. The elimination of these confounders increased overall probability of detection of CysC in association with decreased PCio.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoid therapy benefits in the treatment of CanL have been described previously [20,25,26]. It is worth mentioning that several studies have shown that the short-or long-term oral glucocorticoid administration in dogs do not induce significant changes in the several hematological and biochemical parameters [64][65][66][67]. The four-week course of prednisolone did not seem to have interfered with the biomarkers evaluated herein, as evaluations at T1 did not behave differently than those seen at subsequent follow-up points, as demonstrated in Figures 2-4.…”
Section: Discussionmentioning
confidence: 96%